Consistency in boldness expression varies with ecological context in a jumping spider. (7th August 2019) - Chang, Chia‐chen; Klomp, Danielle A.; Norma‐Rashid, Yusoff; Li, Daiqin
Abstract: Animals can adjust their behaviours depending on ecological context (i.e., behavioural plasticity), and an individual's response to a given context may also vary from occasion to occasion (intra‐individual variability). Recognizing the roles of both behavioural plasticity and intra‐individual variability is important in understanding how behavioural diversity is maintained within populations. However, how the ecological context itself influences the individual behavioural response and intra‐individual variability (e.g., how variable an individual is in their behavioural expression) remains largely unexplored. Here, we examine boldness expression (the duration of startle response) in a specialised spider‐eating jumping spider, Portia labiata, across three contexts following a mild disturbance: presence of a conspecific intruder (most dangerous), environmental change but no conspecific intruder, and no conspecific intruder or environmental change (safest). We found that context does not significantly influence the average boldness expression at the population level. However, each individual responded to each context differently, and the repeatability of boldness expression—the proportion of behavioural variation attributable to the between ‐individual level—is context‐dependent. We also found that in the presence of a conspecific intruder, spiders behave less predictably than in the environmental change context, but not differently from the safest context. These findings may suggest that the presence of conspecifics influences behavioural consistency in individuals, but that this may occur without influencing the population average behaviour.